Effect of familiar and unfamiliar riders on Cortisol, Oxytocin and Beta–endorphin levels in horses - Nergis Ulas; Omer Aydin; Sumeyye Baysal; Mustafa Ileriturk; Omer Eltas (Revista Científica)
Stress response of the horse may be related to the behavioral and physiologic factors e.g., stress hormones. The aim of this study was to evaluate the different rider contact on the stress hormones of the horses that are used for javelin sport in a local riding club. Seven Arabian horses were ridden by familiar riders with the horses in the first and second weeks and by additional unfamiliar riders with the horses in the third and fourth weeks. Cortisol, oxytocin and beta–endorphin levels in sera samples and cortisol levels in saliva were measured before and after the riding. There was no statistical difference in serum cortisol and β–endorphin and salivary cortisol values between the groups with regard to the familiarity (P>0.05). Behavioral scoring did not differ between the groups. However, there was an increase in the oxytocin level of the horses ridden by the familiar riders in the second week compared with the first week (P<0.05). The horses did not respond stressfully associated with the hormone levels and behavioral changes; besides, they responded well to the familiar riders by elevating the oxytocin level. In conclusion, the horses used herein responded well to the familiar and unfamiliar riders with regard to potential stress factors. It has been therefore suggested that the familiarity towards the interaction between the human and the horse may not alter the physiological stress of the horses that are regularly ridden by various people in a riding club.